2017
DOI: 10.1016/j.jce.2016.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Love, money, and parental goods: Does parental matchmaking matter?

Abstract: , and participants at the Chicago-Renmin symposium on family and labor economics at the University of Chicago, the symposium of the 80th birthday of Steven Cheung at Shenzhen, U. of Maryland workshop, the AEA meetings, the PAA conference, and the Asian Conference on Applied Micro-Economics/Econometrics at Tokyo for constructive comment and suggestions. We are especially grateful to the late Gary Becker for his detailed comments at the Chicago-Remin symposium in which we presented an earlier version of a relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 26 publications
(36 reference statements)
0
10
0
Order By: Relevance
“…Arranged marriages were the dominant tradition in China for centuries: parents chose the spouse for their child, often with the help of a professional matchmaker (Huang, Jin, & Xu, ; Xia & Zhou, ; Xie & Combs, ). Since the beginning of the 20th century, a combination of increasing wage labour in China's cities and growing Western influence on China's culture and educational system began to promote young people's choices in mating decisions (Pimentel, ; Xiaohe & Whyte, ; Xie & Combs, ).…”
Section: Introductionmentioning
confidence: 99%
“…Arranged marriages were the dominant tradition in China for centuries: parents chose the spouse for their child, often with the help of a professional matchmaker (Huang, Jin, & Xu, ; Xia & Zhou, ; Xie & Combs, ). Since the beginning of the 20th century, a combination of increasing wage labour in China's cities and growing Western influence on China's culture and educational system began to promote young people's choices in mating decisions (Pimentel, ; Xiaohe & Whyte, ; Xie & Combs, ).…”
Section: Introductionmentioning
confidence: 99%
“…In the Chinese context, Huang, Jin, and Xu [2012] find that couples that were introduced to each other by their parents or another relative have a higher cumulative income, but lower marital harmony. Huang, Jin, and Xu [2016] add that couples that rely on their parents for finding a spouse have more children.…”
Section: Links With the Literaturementioning
confidence: 99%
“…For centuries, arranged marriage had been dominant. Parents chose the spouse for their child, often with the help of a professional matchmaker (Huang, Jin, and Xu 2016;Xia and Zhou 2003). After the Chinese Communist Party came to power the government passed the Marriage Law, adopted in 1950, making arranged marriage illegal.…”
Section: Parental Involvement In Marriage Decisions In Chinamentioning
confidence: 99%
“…Huang et al (2012) used Chinese data to conduct empirical research, and the results showed that free love was happier. Furthermore, Huang et al (2017) established a theoretical model of marriage matching, which divided the matching methods into free love and parental participation. They found that couples whose parents participated in marriage matching took care of their parents more after marriage, but this filial piety was at the expense of the happiness of the couple, which was consistent with Becker et al (2016).…”
Section: Literature Review and Hypothesismentioning
confidence: 99%